2020
DOI: 10.1039/d0re00023j
|View full text |Cite
|
Sign up to set email alerts
|

Studying key processes related to CO2 underground storage at the pore scale using high pressure micromodels

Abstract: Micromodels experimentation for studying and understanding CO2 geological storage mechanisms at the pore scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 245 publications
(287 reference statements)
0
16
0
Order By: Relevance
“…With the help of micromodel experiments, CO 2 diffusion and convective mixing into different pore arrangements can be investigated. Morais, et al [40] conducted an extensive review of key processes related to CO 2 underground storage at the pore scale using high-pressure micromodels. In this experimental study, we observed CO 2 convective mixing, using a micromodel apparatus at reservoir representative pressure and temperature conditions (i.e., at 100 bar and 50 • C, respectively), in both a 100% water saturation system and a residual oil-saturated system.…”
Section: Methodsmentioning
confidence: 99%
“…With the help of micromodel experiments, CO 2 diffusion and convective mixing into different pore arrangements can be investigated. Morais, et al [40] conducted an extensive review of key processes related to CO 2 underground storage at the pore scale using high-pressure micromodels. In this experimental study, we observed CO 2 convective mixing, using a micromodel apparatus at reservoir representative pressure and temperature conditions (i.e., at 100 bar and 50 • C, respectively), in both a 100% water saturation system and a residual oil-saturated system.…”
Section: Methodsmentioning
confidence: 99%
“…For more direct comparisons with geological materials, micromodels can be constructed of minerals, rocks, or other geomaterials (Gerami et al, 2017;Mohammadi & Mahani, 2020;Porter et al, 2015;Y. Song et al, 2012), operated at high pressure and temperature conditions (Morais et al, 2020;Porter et al, 2015), or operated with applied normal stress (Detwiler, 2008). These systems have been used to assess a wide variety of phenomena, including the impact of dissolution and stress (Detwiler, 2008); dissolution/precipitation under multiphase flow conditions (Jiménez-Martínez et al, 2020); turbulent flow and chemical reactions (Lee & Kang, 2020); gravity-driven homogeneous precipitation in a fracture (Jiménez-Martínez et al, 2020), and multiphase flow (Keller et al, 1997).…”
Section: Transparent Analog Systems and Microfluidicsmentioning
confidence: 99%
“…Extensively characterized surface modification properties based on the silanol group (−Si–OH), along with chemical resistance and flexibility in design, makes silicon a desirable material for the fabrication of microfluidic devices . Moreover, silicon-based micromodels are better than glass-based micromodels for better quality control and high geometry resolution while still keeping the merits of glass, such as good chemical stability and feasible wettability alteration . Further, silicon can withstand temperatures as high as 1400 °C and high elastic modulus (130–180 GPa) .…”
Section: Micro/nanofluidic Materialsmentioning
confidence: 99%